Coral Reef Electrotherapy: Field Observations - Goreau, Thomas J. F. (Frontiers in Marine Science, 2022)
Coral reefs are the fastest collapsing ecosystems from accelerating global warming, sea level rise, disease, and pollution. Urgent steps are essential to regenerate them, and their biodiversity and environmental services, if there is to be a sustainable “Blue Economy”. Methods that greatly increase settlement, growth, survival, and resistance to extreme high temperature and pollutant stress are critically needed to regenerate coral reef and coastal ecosystems now and for the future. Safe Extremely Low Voltage (SELV) electrical fields generated by the Biorock electrolytic reef process have been documented for more than 35 years to greatly increase settlement, growth, healing, and survival of marine organisms in general under extreme stress conditions. The visibly observable benefits of electrical stress relief on marine organisms are summarized, and testable hypotheses proposed to determine mechanisms and improve applications. Although these field observations strongly imply that electricity in the right range improves stress resistance and health, the mechanisms have never been studied at cellular, biophysical, or biochemical levels. Electrical stimulation is the only method known to reverse impacts of extreme stresses on corals and other marine organisms, so widespread regeneration of coral reef ecosystems by electrotherapy is urgently needed before they become functionally extinct.